2022
DOI: 10.1111/ppl.13761
|View full text |Cite
|
Sign up to set email alerts
|

Foliar‐applied manganese and phosphorus in deficient barley: Linking absorption pathways and leaf nutrient status

Abstract: Foliar fertilization delivers essential nutrients directly to plant tissues, reducing excessive soil fertilizer applications that can lead to eutrophication following nutrient leaching. Foliar nutrient absorption is a dynamic process affected by leaf surface structure and composition, plant nutrient status, and ion physicochemical properties. We applied multiple methods to study the foliar absorption behaviors of manganese (Mn) and phosphorus (P) in nutrient‐deficient spring barley (Hordeum vulgare) at two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 68 publications
(126 reference statements)
0
20
1
Order By: Relevance
“…Nevertheless, CO 2 assimilation was increased by about 85%, indicating that P-deficient maize plants are not fundamentally incapable of recovering plant functionality, but that the uptake of P via the leaf is the limiting factor. In the study of Arsic et al [ 53 ], P deficient barley plants ( Hordeum vulgare ) were also unable to restore photosynthetic processes after foliar P treatment. As suggested by the authors, one reason was the altered morphology of the plant under P deficiency, which showed no influence on stomatal or trichome density, unlike in Fernández et al [ 25 ], but a thicker cuticle and epidermal cell wall with lower abundance of polysaccharides, all of which are characteristics that are connected to impaired foliar uptake [ 31 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, CO 2 assimilation was increased by about 85%, indicating that P-deficient maize plants are not fundamentally incapable of recovering plant functionality, but that the uptake of P via the leaf is the limiting factor. In the study of Arsic et al [ 53 ], P deficient barley plants ( Hordeum vulgare ) were also unable to restore photosynthetic processes after foliar P treatment. As suggested by the authors, one reason was the altered morphology of the plant under P deficiency, which showed no influence on stomatal or trichome density, unlike in Fernández et al [ 25 ], but a thicker cuticle and epidermal cell wall with lower abundance of polysaccharides, all of which are characteristics that are connected to impaired foliar uptake [ 31 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the effects on biomass formation, adequate timing, as well as the optimal concentration of foliar P application were the focus of investigations. In recent years, some foliar P application studies were carried out with P deficient plant species such as wheat [ 25 , 48 , 49 , 50 , 51 , 52 ], barley [ 20 , 21 , 53 , 54 , 55 ] or maize [ 28 , 56 , 57 ]. It was shown that P deficiency can lead to alterations in the composition of plant tissues and epidermal structures such as stomata and trichomes, which ultimately affects the rate of uptake of P via foliage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A large number of idioblast cells filled with water in a leaf, in particular, could have several effects on leaf-water relation parameters. Idioblasts potentially alter (1) bulk leaf osmotic potential, (2) the water potential at the turgor pressure deficit loci, (3) hydraulic capacitance, (4) transpiration forces in action, and (5) the hydraulic drifts promoting water uptake in plants (Sruthi and Puthur 2020;Arsic et al 2022). Transpiration pull, water capacitance and osmotic potential are remarkably crucial for succulents.…”
Section: Resultsmentioning
confidence: 99%